2018
DOI: 10.1016/j.rcim.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Robotic disassembly for increased recovery of strategically important materials from electrical vehicles

Abstract: The rapid growth of market share of Electrical Vehicles (EVs) and their increasing amount of electric and electronic components have introduced difficult challenges for future recycling of such vehicles. End of Life Vehicles (ELVs), together with Waste from Electric and Electronic Equipment (WEEE), are renowned as an important source of secondary raw materials. In addition, a significant proportion of the hidden value at the End-of-Life (EoL) of the EVs is embedded in the light fractions containing complex mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…To alleviate the aforementioned risks and to extend laboratory-based methods to suit the growing recycling industry for EV batteries, there are very few published patents and research studies about possibility of automating the procedure of dismantling of EV battery packs, sorting and battery measurement. However, the focus is more on the robot-assisted disassembly [45][46][47] and design of flexible tools that can be used for disassembly. 48 Hedegor et al developed a battery testing and sorting system that sorts the batteries based on the electrical condition of the batteries.…”
Section: Rationale For Automating the Eis Testmentioning
confidence: 99%
“…To alleviate the aforementioned risks and to extend laboratory-based methods to suit the growing recycling industry for EV batteries, there are very few published patents and research studies about possibility of automating the procedure of dismantling of EV battery packs, sorting and battery measurement. However, the focus is more on the robot-assisted disassembly [45][46][47] and design of flexible tools that can be used for disassembly. 48 Hedegor et al developed a battery testing and sorting system that sorts the batteries based on the electrical condition of the batteries.…”
Section: Rationale For Automating the Eis Testmentioning
confidence: 99%
“…A new research trend observed in recent years (from 2012–2019) is the disassembly of electric vehicle components , , , , , . Apart from the robot applications, WEEE is also targeted on a theoretical level.…”
Section: Content Analysis and Classificationmentioning
confidence: 99%
“…Finally, other experts focus on power electronics [44,45]. Here, a robotized workstation is proposed for the automatic disassembly of electronic components from EV batteries before their final recycling.…”
Section: Battery Engine Electronicsmentioning
confidence: 99%